Membrane Fouling and Chemical Cleaning in Three Full-Scale Reverse Osmosis Plants Producing Demineralized Water - Florian Beyer; Judita Laurinonyte; Arie Zwijnenburg; Alfons J. M. Stams; Caroline M. Plugge (Journal of Engineering)
Membrane fouling and cleaning were studied in three reverse osmosis (RO) plants. Feed water was secondary wastewater effluent, river water, and surface water. Membrane autopsies were used for fouling characterization. Fouling layer measurements included total organic carbon (TOC), adenosine triphosphate, polysaccharides, proteins, and heterotrophic plate counts. In all locations, membrane and spacer fouling was (bio)organic. Plant chemical cleaning efficiencies were evaluated from full-scale operational data and cleaning trials in a laboratory setup. Standard cleaning procedures were compared to two cleaning procedures specifically adapted to treat (bio)organic fouling using commercial blend cleaners (mixtures of active substances). The three RO plants were impacted by irreversible foulants causing permanently decreased performance in normalized pressure drop and water permeability even after thorough chemical cleaning. The standard plant and adapted cleaning procedures reduced the TOC by 45% on average, with a maximum of ~80%. In general, around 20% higher biomass removal could be achieved with adapted procedure I compared to adapted procedure II. TOC measurements and SEM showed that none of cleaning procedures applied could remove foulants completely from the membrane elements. This study underlines the need for novel cleaning approaches targeting resistant foulants, as none of the procedures applied resulted in highly effective membrane regeneration.